Public policies of higher education in Chile in crisis contexts: Transformations and continuities of the university system between the Civil-Military Dictatorship and the Post-Dictatorship (1981-2018) - Zurita, Felipe (Education Policy Analysis Archives, 2022)
The objective of this article is to analyze the university public policy built and implemented between the Civil-Military Dictatorship and the Post-Dictatorship in Chile, with the special interest of identifying and analyzing the transformations and continuities developed on this problem in said period. To achieve this objective, a methodology of historiographic study organized around the collection and analysis of legal sources and strategic documents of the state was defined. The results of the study made it possible to identify visible trends of continuity in university public policy between these historical periods, a scenario that began to be challenged by the eruption of the student movement in public discussions about the configuration of the university system in the first decades of the 21st century, opening the way to complex challenges for the present and future of this system.